Postoperatif ağrı ve hemşirelik uygulamaları - (:unkn) unknown (My University, 2010)
Amaç: Cerrahi girişimlerin önemli bir ağrı nedeni olduğu bilinmektedir. Ağrı algısı yaş, gelişim dönemleri, önceki ağrı deneyimleri ve diğer çevresel faktörlerle ilişkilidir. Postoperatif ağrı düzeyi farklı farmakolojik ve nonfarmakolojik tekniklerle azaltılabilir. Bu araştırma, ağrı probleminde uygulanan hemşirelik uygulamalarını belirlemek amacı ile yapıldı. Gereç ve Yöntem: Araştırmaya, cerrahi kliniklerinde çalışan 189 hemşire katıldı. Araştırmacılar tarafından hazırlanmış olan soru formu ile hemşirelerin demografik özellikleri ve ağrı probleminde uyguladıkları aktiviteler belirlendi. Bulgular: Sonuçlar, 146 hemşirenin (%77.2) ağrıyı azaltmak için en sık analjezik uyguladıklarını göstermiştir. Sonuç: Ağrı yönetiminde kullanılan diğer hemşirelik uygulamaları; hasta kontrollü analjezi (HKA), masaj, görsel kıyaslama ölçeği (GKÖ), gevşeme tekniklerini öğretme, harekete yardım etme ve yaşam bulgularını değerlendirmedir.

Objectives: Surgery is recognized as an important cause of pain. Expression of pain differs according to age, developmental stage, previous pain experiences, and other modifying environmental factors. The degree of postoperative pain should be reduced using different techniques, both pharmacological and non-pharmacological. This study aimed to determine the effects of various actions taken by nurses for the purpose of pain management. Methods: One hundred eighty-nine nurses working in the surgical ward were included in this study. A questionnaire was used to investigate demographic data and the actions taken by the nurses in the study group to alleviate pain. Results: The results showed that 146 of 189 nurses (77.2%) administered analgesic medication more often than employing other techniques for pain management. Conclusion: The other applications in pain management included patient-controlled analgesia (PCA), massage, visual analog scale (VAS), and teaching relaxation techniques, helping with mobilization, and assessing vital signs.
Approaches taken by nurses in treating postoperative pain
Keywords: Genel ve Dahili Tıp; Kadın Hastalıkları ve Doğum; Temel Sağlık Hizmetleri; Cerrahi; Hemşirelik